Unpacking road safety at a district level - the case of Cape Town, South Africa - Janmohammed, Aliasgher M (Department of Civil Engineering, 2018)
In South Africa, the legacy of apartheid planning established vast differences within cities in terms of household income, consequently, the population in different areas are exposed to varying road environments. These road environments include, for instance, the mode usage of the population that exposes them to varying traffic conditions. The literature suggests that there is a need to understand road fatalities further, so as to articulate informed interventions by determining the impact of these environments on road fatalities, at a more disaggregated level than that of cities. With road fatality levels remaining high within the country, this study aims to perform this disaggregated study for Cape Town. In this study, Cape Town fatality data for the 2011-2015 period was analysed on a 2013 Traffic Analysis Zone level, defined in this study as the analysis district. The analysis included determining absolute fatalities and fatality rates, comparing mode usage with fatalities, and imputing the mode involved in fatalities. Geocoded data was also used to extract the top 10 hazardous zones in the city by ranking them based on the number of road fatalities and describing the fatality conditions in the top three zones. Analysis revealed that pedestrians constitute the majority of road fatalities in the city (58%) and all analysis districts. Furthermore, the low-income districts had a high road fatality burden per annum, but a low fatality rate that was comparable to high-income countries. Alternatively, high-income districts had a low road fatality burden per annum, but a high fatality rate. It was also found that percentage fatalities that impact pedestrians and cyclists are more than the percentage of the population that walk and cycle in the city. In terms of modes involved in fatalities, the Forensic Pathology Services data contained a large percentage of missing data (54%) hence, the analysis showed inconclusive results. Lastly, geocoded data revealed that the top three hazardous zones in the city - N1 and N7 junction, Table Bay Boulevard (N1) and M30 and R101 junction - continue to impact pedestrians crossing highspeed arterials. The dataset also suggested that risky driver behaviour and lighting is a major problem in these zones. From the results, it can be inferred that the prescribed interventions need to target pedestrian fatalities at both an aggregated and a disaggregated level. In the case of the hazardous zones, these localised interventions need to include reducing speed limits along residential roads, providing adequate lighting and creating safe pedestrian crossing facilities along desire lines. Moreover, both, average annual fatalities and fatality rates, need to be determined when prioritising areas for road safety measures. Lastly, given the percentage of missing data, the fatality burden in the city is underrepresented, which suggests there is a need to improve data capturing in the field. While this study has been adopted towards the Cape Town context, the principles of this study can be implemented in countries with high fatality burdens, which mainly include low- and middle-income countries.